Intramural Gas: Would it be Life-threatening? - Azna Aishath Ali; Syamim Johan; Firdaus Hayati; Chiak Yot Ng (2020)
The CECT scan of the abdomen at axial and coronal views show gas bubbles tracking along the inner wall of the ascending colon and hepatic flexure, which is separated from the intraluminal gas within the bowel. These intramural gas bubbles appear to be outlining the bowel wall circumferentially. The bowel wall appears to be thickened however the inner mucosa is not enhanced. There are no ascites in the images provided. The colon of the hepatic flexure and transverse colon appears dilated. No significant atherosclerotic plaque in the visualised arteries. Based on the clinical presentations and CECT features in Figure 1 and Figure 2, the best diagnosis for him is benign pneumatosis intestinalis (PI) secondary to obstructed low rectal cancer. He was subjected for a trephine transverse colostomy to relieve the obstruction with simultaneous transanal rectal mass biopsy. Once the histology is available, he subsequently will be referred for concurrent chemo-radiotherapy as neoadjuvant treatment and later for a low anterior resection, provided that it is a localized disease.